Diagnostic accuracy of post mortem MRI for abdominal abnormalities in foetuses and children. Issue 3 (March 2015) - Arthurs, Owen J.; Thayyil, Sudhin; Owens, Catherine M.; Olsen, Oystein E.; Wade, Angie; Addison, Shea; Jones, Rod; Norman, Wendy; Scott, Rosemary J.; Robertson, Nicola J.; Taylor, Andrew M.; Chitty, Lyn S.; et al.
Highlights: Postmortem MR imaging (PMMR) has high overall accuracy for abdominal pathology in foetuses, newborns and children. PMMR is particularly good at detecting renal abnormalities, and relatively poor at detecting intestinal abnormalities. In clinical practice, PMMR may be a useful alternative or adjunct to conventional autopsy in foetuses and children for detecting abdominal abnormalities. Abstract: Background: To compare the diagnostic accuracy of post-mortem magnetic resonance imaging (PMMR) specifically for abdominal pathology in foetuses and children, compared to conventional autopsy. Methods: Institutional ethics approval and parental consent was obtained. 400 unselected foetuses and children underwent PMMR using a 1.5 T Siemens Avanto MR scanner before conventional autopsy. PMMR images and autopsy findings were reported blinded to the other data respectively. Results: Abdominal abnormalities were found in 70/400 (12%) autopsies. Overall sensitivity and specificity (95% confidence interval) of PMMR for abdominal pathology was 72.5% (61.0, 81.6) and 90.8% (87.0, 93.6), with positive (PPV) and negative predictive values (NPV) of 64.1% (53.0, 73.9) and 93.6% (90.2, 95.8) respectively. PMMR was good at detecting renal abnormalities (sensitivity 80%), particularly in foetuses, and relatively poor at detecting intestinal abnormalities (sensitivity 50%). Overall accuracy was 87.4% (83.6, 90.4). Conclusions: PMMR has high overall accuracy for abdominal pathology in foetuses, newborns and children. PMMR is particularly good at detecting renal abnormalities, and relatively poor at detecting intestinal abnormalities. In clinical practice, PMMR may be a useful alternative or adjunct to conventional autopsy in foetuses and children for detecting abdominal abnormalities.